Jejak Moderasi Beragama di Kesultanan Aceh di bawah Pemerintahan Sultanah Safiatuddin - Gumilar Irfanullah; Varidlo Fuad (Jurnal Tamaddun, 2022)
This paper discusses the traces of religious moderation, inclusivicity and tolerant policies during the reign of the sultan Sri Tajul Alam Safiatuddin. Starting from the conflict and religious polemics in Aceh during the Iskandar Thani administration, who supported ar-Raniri's resistance to religious beliefs which he considered deviant, Safiatuddin fought them by issuing policies that led to the formation of a more tolerant, inclusive, and non-violent attitude. Safiatuddin did this by fully supporting moderate scholars such as Sheikh Abdur Rauf Singkel. This paper uses a theory about the effect of education on a person's level of tolerance and acceptences, which can trace the reasons behind Safiatuddin's policies in favor of tolerance and inclusivism. Using historical methods and literature studies, this study finds that after Iskandar Thani and ar-Raniri's return to his home country in India, Aceh's religious life is relatively harmonious and inclusive. Abdur Rauf Singkel wrote many books and essays that mediate polemic religious discourses. Abdur Rauf's efforts are fully supported by Safiatuddin, who also believes that a moderate attitude can maintain political stability and harmony in religious life in society despite various differences in religious interpretation.